Frontiers in complex dynamics : in celebration of John Milnor's 80th birthday - Milnor, John W. (John Willard), 1931-; Bonifant, Araceli, 1963-; Lyubich, Mikhail, 1959-; Sutherland, Scott (Princeton mathematical series, 2014)
John Milnor, best known for his work in differential topology, K-theory, and dynamical systems, is one of only three mathematicians to have won the Fields medal, the Abel prize, and the Wolf prize, and is the only one to have received all three of the Leroy P. Steele prizes. In honor of his eightieth birthday, this book gathers together surveys and papers inspired by Milnor's work, from distinguished experts examining not only holomorphic dynamics in one and several variables, but also differential geometry, entropy theory, and combinatorial group theory.